Modos de vida e convívio escolar : o assentamento rural Santa Helena - São Carlos - SP - Mateus, Kergilêda Ambrosio de Oliveira (Universidade Federal de São Carlos, 2016)
This work is a result of various concerns that have marked the personal and professional life of the researcher. We undertook efforts to investigate the social practice of the School Life of adult students who attend the Novo Horizonte School located in rural settlement called Santa Helena in São Carlos city - São Paulo state - and we seek to answer which educational processes are emerging from this social practice. To understand how seated teenagers and adults are educated regarding the social practice of the School Life; to describe those educational process and to analyze the meanings of this social practice in the life of its participants, we opted to utilize a methodological approach with a qualitative focus guided by a participative research. To collect the data, we used informal notes, informal chats and semi-structured interviews. As a result of this study, we identified that: participate in the struggle for a place to live is a way to educate; the absent of schooling does not mean the removal of fundamental knowledge for the life of the settlers of Santa Helena; the school life is configured as an important tool for strengthening the bonds of those who attends the literacy room of Novo Horizonte school, identified as a place for meetings and for the promotion of sociability; the field requires a different kind of school that promotes sociability of their subjects and respect their way of life, which should serve as a basis for their schooling. We hope that this work provokes new reflections about the social practice of the School Life and the way of life of men and women in rural settlements and, from these considerations, the resizing of new and other pedagogical approaches that consider their social and political reality and perceptions, desires and educational needs of these individuals.
Keywords: Processos educativos; Convívio Escolar; Sociabilidade; Luta pela terra; Educação de Jovens e Adultos; Educational processes; School Life; Sociability; Struggle for a place to live; Youth and Adult Education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::ORIENTACAO E ACONSELHAMENTO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL